PHYSICOCHEMICAL DIFFERENCES BETWEEN FRAGMENTS OF PLASMA MEMBRANE AND ENDOPLASMIC RETICULUM - Wallach, Donald F. Hoelzl (The Rockefeller University Press, 1966)
Specific turbidities, densities, and refractive indices of fragments of plasma membrane (PM) and endoplasmic reticulum (ER) from Ehrlich ascites carcinoma have been measured. A spherical shell model of specified dimensions and refractive index was established for PM fragments. The ionic composition of the dispersion medium was varied systematically. Increases in Γ/2 caused increases in the turbidity of both PM and ER suspensions, the greatest effects being observed with Ca(2+) and Mg(2+). In the case of PM this effect is attributable mainly to aggregation, whereas "structural" changes account for most of the turbidity increase with ER. The pH was also varied systematically to obtain pH- density and turbidity profiles and to establish the isoelectric pH of the two membrane types (PM—3.6; ER—4.35). Turbidity was maximum at "isoelectric" pH, which corresponds in each case to the region of minimum charge on the particle surfaces. Both PM and ER show large increases of density at the "isoelectric" pH, but only ER shows substantial structurally based turbidity increase under these conditions. Both PM and ER show operation of electrostatic attractions near "isoelectric" pH. PM has been shown to have ionically distinctive inner and outer surfaces while ER shows no such dissymmetry. The necessary theoretical background for interpretation of turbidity and density measurements is included, as well as a discussion of the limitations of our conclusions and the biological importance of our results.